Factors influencing sialorrhea in orally intubated patients: a lasso and logistic regression analysis - Du, Jinlei; Wang, Min; Wu, Xiaoling; Yu, Tianbo; Zhang, Jiquan; Wu, Jimin (Frontiers in Medicine, 2025)
ObjectiveTo investigate the prevalence of sialorrhea in orally intubated patients and systematically analyze its influencing factors.MethodsA cross-sectional study was conducted from March 15 to 31, 2025, involving 40 tertiary general hospitals across 10 prefecture-level cities in Sichuan Province, including Chengdu, Zigong, and Mianyang. The investigation assessed the current status of sialorrhea in patients undergoing oral endotracheal intubation.ResultsA total of 453 questionnaires were collected, of which 440 were valid, yielding an effective response rate of 97.0%. Statistical analysis revealed that the incidence rate of sialorrhea among orally intubated patients was 27.27%. Multivariate logistic regression analysis identified the following as independent risk factors for sialorrhea: Body Mass Index (BMI) (OR = 1.365, 95% CI: 1.217–1.531), Smoking (OR = 8.944, 95% CI: 4.272–18.727), Number of Combined Functional Impairment Systems (OR = 2.844, 95% CI: 1.814–4.460), Combined Oral Disease (OR = 2.578, 95% CI: 1.240–5.359), and Neurological Diseases (OR = 4.040, 95% CI: 1.053–15.507). A restricted cubic spline analysis further demonstrated that when BMI exceeds 22.785, the risk of developing sialorrhea increases significantly.ConclusionThe incidence of sialorrhea in orally intubated patients is at a moderate-to-low level. This condition is closely associated with elevated BMI, smoking, a higher number of combined functional impairments, the presence of oral disease, and underlying nervous system disorders.